A Hybrid Assessment of Clinical Mobility Test Items for Evaluating Individuals With Mild Traumatic Brain Injury. Issue 2 (19th April 2023) - Fino, Peter C.; Michielutti, Patrick G.; Pelo, Ryan; Parrington, Lucy; Dibble, Leland E.; Hoppes, Carrie W.; Lester, Mark E.; Weightman, Margaret M.; King, Laurie A.
Abstract : Background and Purpose: The Functional Gait Assessment (FGA) and High Level Mobility Assessment Tool (HiMAT) are clinical batteries used to assess people with mild traumatic brain injury (mTBI). However, neither assessment was specifically developed for people with mTBI; the FGA was developed to evaluate vestibular deficits, and the HiMAT was developed for individuals with more severe TBI. To maximize the sensitivity and reduce the time burden of these assessments, the purpose of this study was to determine the combination of FGA and HiMAT items that best discriminates persons with persistent symptoms from mTBI from healthy controls. Methods: Fifty-three symptomatic civilians with persistent symptoms from mTBI (21% male, aged 31 (9.5) years, 328 [267] days since concussion) and 57 healthy adults (28% male, aged 32 (9.6) years) participated across 3 sites. The FGA and HiMAT were evaluated sequentially as part of a larger study. To determine the best combination of items, a lasso-based generalized linear model (glm) was fit to all data. Results: The area under the curve (AUC) for FGA and HiMAT total scores was 0.68 and 0.66, respectively. Lasso regression selected 4 items, including FGA Gait with Horizontal Head Turns and with Pivot Turn, and HiMAT Fast Forward and Backward Walk, and yielded an AUC (95% confidence interval) of 0.71 (0.61-0.79) using standard scoring. Discussion and Conclusions: The results provide initial evidence supporting a reduced, 4-Item Hybrid Assessment of Mobility for mTBI (HAM-4-mTBI) for monitoring individuals with mTBI. Future work should validate the HAM-4-mTBI and investigate its utility for tracking progression throughout rehabilitation. Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A409 ).